Práticas curriculares na RS: as (poli)técnicas de governamento - Felix, Adriani Mello (2013)
This work analyses the historical and discursive conditions of production of curricular reform for High School in Brazil, particularly in Vocational High School Polytechnic. This paper aims at understanding, in the official curricular discourses, how mathematics becomes an important device for conducting subjects via curriculum and public policies addressed by education. This paper discusses the articulations between contextualization, statistical knowledge and mathematics, problematizing its (im)possibilities in such model of curriculum. To do so it was applied Foucault's concept of discursive practices and governmentality. The research used sources from documental analysis with official documents about High School integrated seminar and its Projetos Vivenciais in RS. In order to examine it the author makes some inferences using the concept of polytechnics to approach these projects and their discursive possibilities related to neoliberal governmentality.